Achievement Goal Orientation in Online Learning Is Performance Goal More Important Than Mastery Goal In Farmachy Student? - Herdian; Logisian Subekti, Roseyoana (International Journal of Scientific Research and Management (IJSRM), 2022)
Online learning is still in effect until early 2022. Teachers, students and parents can feel the impact on the educational aspect. We examine students' learning motivation in achievement goal orientation during online learning. A total of 238 pharmacy students filled out the achievement goal orientation scale online. The results show no significant difference in the average of each orientation, including the approach and avoidance dimensions. Our findings illustrate how pharmacy students as part of a collectivist society affect student orientation in achievement goals. The results show that the average performance goal orientation is higher than the mastery goal orientation. The results of the dimensions are discussed in detail.